Social Intelligence and its Relation to School Adaptation among Female Students with Learning Difficulties from Perspective of Instructors and Teachers in Elementary School in Jeddah - Al-otaibi, Omniah Dhaif Allah; Akram, Hadeel Abdullah (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the correlation between social intelligence and school adjustment concerning female students with learning difficulties from the perspective of female guides and teachers at the primary level in Jeddah, as well as knowing the level of social intelligence and school adjustment in addition to checking for differences between averages of the degrees of social intelligence and school adjustment among female students from the perspective of female guides and teachers due to the variable type of profession, scientific specialization and years of experience. The sample of the study consisted of (152) guides and teachers where the researcher followed the descriptive correlation method, and the scale of social intelligence and school adaptation (2020) was used by the researcher. The findings indicated a positive relationship between social intelligence and school adaptation among female students learning difficulties and they have an average level in both social intelligence and school adaptation. In addition, there are no differences between the average scoring of social intelligence and school adaptation among female students of learning difficulties from the point of view of female counselors and teachers due to the variable of profession, scientific specialization and number of years of experience. As a result of the study results, the researcher reached a number of recommendations addressed to educational institutions and female teachers and guides of general education schools applied to learning disabilities programs, which contributes to the development of social intelligence and school adaptation for female students with learning difficulties.
Keywords: Social Intelligence; School Adaptation; Student Learning Difficulties; Female teachers of Learning Difficulties; Guides; Primary School